First record of Berthellina ilisima (Gastropoda: Heterobranchia: Pleurobranchida) in Peruvian waters with its anatomy description - Mendivil, Alejandro (2022)
The Pleurobranchida are sea slugs that group around 100 species distributed in the seas worldwide, but with a greater diversity in tropical and temperate coastal environments. In the Eastern Pacific, 2 families, 4 genera and more than 10 species of Pleurobranchida have been reported. The species Berthellina ilisima Marcus & Marcus 1967 common in the Eastern Tropical Pacific Province is formally recorded in coastal waters of Tumbes, Peru. The anatomy of the digestive, circulatory, reproductive and nervous systems of B. ilisima is described, which constitutes the first description of the internal anatomy of a Pleurobranchida for Peru.